Scope of Artificial Intelligence in Enhancement of Emergency Rescue Services: Future Prospects - Muhammad Iqbal,; Dr. Shandana,; Maria Ghani,; Shams Tabrez,; Aurangzeb Khan Mehsud*, (Al-Qanṭara, 2023)
This research paper aims to determine the scope and use of artificial intelligence (AI) in the development and enhancement of emergency rescue services. The function, use and utilization of Artificial Intelligence is a growing need nowadays. Usage of Artificial Intelligence can revolutionize the emergency rescue service by improving its efficiency, accuracy and especially its response time. AI-driven predictive analytics can do better resource allocation and early identification of disaster-prone areas, by analyzing vast data-sets. Real time information regarding all types of emergencies & disasters, resources including staff & vehicles can be developed & make advanced through algorithms (analysis of statistical data) in AI. Pre-Assessment of emergency hotspots, navigation of hazards, its frequency and intensity can be checked through AI powered drones & robotics. By use of AI protocols, we can develop more quick coordination and communication among rescue workers and other law enforcing agencies on the emergency spot. The AI ongoing evolution and adaptation has the capacity to transform emergency services to leading life-saving interventions and also minimizing the existing & long-term vulnerabilities of different hazards & disasters. It stands as an indispensable element within forthcoming emergency response systems, offering significant potential for reshaping this field. This paper will help the planners & decision makers of emergency rescue service to work with new zeal and enthusiasm, accompanied with advanced technologies. Keywords: Artificial Intelligence, Emergency Rescue Services, Predictive Analytics